Impact of Audio-Visual Aids on the Performance of Grade 1 Students in Science - Rabia khurshid; Asma Zia; Adeel Ahmed Khan (JECCE, 2024)
This study examined that how audio-visual (AV) aids can improve first-grade science students' performance. The objective of this research was to find out how well AV aids may enhance students' performance and learning. For this study, a quasi-experimental research design was employed. The participants for this research were 20 students of grade 1. A test composed of multiple-choice questions was used as a research instrument. The research found that the group used AV aids during teaching performed better than the group that received traditional lectures during teaching. Based on the findings, it is suggested that AV aids may be a useful tool for helping young children to understand the subject of science.